Spinal protein kinase A and phosphorylated extracellular signal-regulated kinase signaling are involved in the antinociceptive effect of phytohormone abscisic acid in rats - MOLLASHAHI, Mahtab; ABBASNEJAD, Mehdi; ESMAEILI-MAHANI, Saeed (Arquivos de Neuro-Psiquiatria, 2020)
Objective: The phytohormone abscisic acid (ABA) as a signaling molecule exists in various types of organisms from early multicellular to animal cells and tissues. It has been demonstrated that ABA has an antinociceptive effect in rodents. The present study was designed to assess the possible role of PKA and phosphorylated ERK (p-ERK) on the antinociceptive effects of intrathecal (i.t.) ABA in male Wistar rats. Methods: The animals were cannulated intrathecally and divided into different experimental groups (n=6‒7): Control (no surgery), vehicle (received ABA vehicle), ABA-treated groups (received ABA in doses of 10 or 20 µg/rat), ABA plus H.89 (PKA inhibitor)-treated group which received the inhibitor 15 min prior to the ABA injection. Tail-flick and hot-plate tests were used as acute nociceptive stimulators to assess ABA analgesic effects. p-ERK was evaluated in the dorsal portion of the spinal cord using immunoblotting. Results: Data showed that a microinjection of ABA (10 and 20 µg/rat, i.t.) significantly increased the nociceptive threshold in tail flick and hot plate tests. The application of PKA inhibitor (H.89, 100 nM/rat) significantly inhibited ABA-induced analgesic effects. Expression of p-ERK was significantly decreased in ABA-injected animals, which were not observed in the ABA+H.89-treated group. Conclusions: Overall, i.t. administration of ABA (10 µg/rat) induced analgesia and p-ERK down-expression likely by involving the PKA-dependent mechanism.
Keywords: abscisic acid; anti-nociception; PKA; p-ERK; rats